Against the odds? Keeping a nontraditional division of domestic work after first parenthood in Spain. - Dominguez-Folgueras, Marta; Jurado-Guerrero, Teresa; Botía-Morillas, Carmen (Journal of Family Issues, 2018)
This article analyzes changes in the division of routine domestic work after first parenthood. We wanted to know whether and how it was possible for couples to resist the trend toward traditionalization that has been shown in the literature. To do so, we analyze semistructured interviews with 27 Spanish couples who were expecting their first child in 2011 and interviewed them again in 2013. The couples were selected from a bigger sample because of their nontraditional practices preparenthood. Our results show that 17 of them were able to maintain a nontraditional division of domestic work, whereas 10 traditionalized. In our analysis, relative resources and time availability did not sufficiently explain the changes in the division of work, but specific characteristics of the division of work before childbirth—men’s active participation, the routinization of tasks, and flexible standards—emerged as key factors to resist the trend toward more traditional arrangements. © 2017, © The Author(s) 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; discipline; division sexuelle du travail; espagne; europe; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique

Les solidarités familiales sous l’angle du travail: un siècle au Québec - Kempeneers, Marianne; Van Pevenage, Isabelle; Dandurand, Renée B. (Nouvelles Questions Féministes, 2018)
Les femmes sont le pivot des solidarités familiales, c’est un fait solidement documenté. Malgré cette évidence empirique, les solidarités familiales n’occupent qu’une place fort discrète dans l’univers théorique des rapports sociaux de sexe, contrairement par exemple au travail domestique ou, plus récemment, au travail du care. Les auteures s’interrogent ici sur cet état de fait. Elles proposent ensuite une lecture des solidarités familiales avec, pour ancrage, le paradigme fondateur que constitua la refonte du concept de travail par les courants féministes matérialistes. Adoptant une perspective historique et macrosociologique, cet article est l’occasion de prendre du recul face à un certain nombre de résultats issus d’une vaste enquête que les auteures avaient menée en 2004 sur les transformations des solidarités familiales au Québec au long du XXe siècle. La profondeur historique de cette enquête fait en sorte que ces données, bien que recueillies en 2004, restent pertinentes pour leur propos, à savoir jeter un éclairage sur les logiques reliant les évolutions concomitantes des solidarités familiales, du travail des femmes et des politiques publiques au Québec durant ce siècle crucial de son histoire.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; famille; histoire et politique; hétérosexualité; inégalités; maternité; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Apprendre l'usage du temps dans les familles cadres: Une enquête en immersion. - Ponsin, Annabelle (Enfances, Familles, Generations, 2018)
Cadre de la recherche : Les pratiques de gestion de parents cadres expriment la normativité des rationalités managériales. Celles-ci renvoie à des raisonnements gestionnaires transversales (sphères privées ou publiques, familiales ou professionnelles, de loisirs) qui dessinent des rapports à soi, aux autres, et au monde (Le Texier, 2016). L’articulation des temps quotidiens (Kaufmann, 1992) et des trajectoires de vie (Bessin 2009) permet de saisir les rapports de classe, d’âge et de genre (Le Feuvre, 2006) en jeu dans ces processus. Les normes temporelles y sont « bricolées » et continuellement rejouées (Canguilhem, 1943 ; De Certeau 1994). Objectifs : J’observe la manière dont ces « temporalités managériales » sont modelées, intériorisées et transmises par les membres du couple (dans leurs vies professionnelles, parentales, conjugales), les enfants (dans leur socialisation, leur scolarité, leur mobilité) et les collectifs familiaux (dans leurs modes de gestion quotidienne). Méthodologie : L’approche qualitative s’amorce par une immersion. En tant que baby-sitter, je remplis un triple rôle : fonctionnel (pour coordonner les activités), éducatif (pour socialiser les enfants à l’enchainement de ces activités) et affectif (pour temporiser les cadences de ces rythmes). Cette immersion se complète par un dispositif d’entretiens et de carnets de bord personnalisés. Résultats : Ces foyers sont des interfaces, semi-ouvertes, de flux. La place que j’y prends est charnière pour comprendre le rôle nodal des mères et des normes éducatives dans la production, la diffusion, l’intériorisation et l’invisibilisation des normes temporelles. Conclusion : Les « modalités de construction » de ces temporalités (Elias, 1997) informent des normativités managériales qui se logent dans nos modes d’être et nos co-constructions intimes. Contribution : L’immersion dans ces territoires temporels, que j’apprivoise, est une clef pour saisir ces processus en leur cœur. Par un retour réflexif sur ma pratique itérative, cet article souligne les co-constructions familiales de normes temporelles managériales.
Keywords: 2000 à aujourd'hui; 2010-2019; care; charge mentale; discipline; europe; france; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail du care

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Prendre en compte les femmes à bas salaires et racisées - Yerochewski, Carole (Nouveaux Cahiers du socialisme, 2018)
Keywords: amériques; approches et analyses; care; cours; discipline; fem1300; inégalités; mouvement syndical; mouvements des femmes*; premier cycle; québec; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail